The effect of a proprioceptive balance board training program for the prevention of ankle sprains - Verhagen, E.; van der Beek, A.; Twisk, J.; Bouter, L.; Bahr, R.; van Mechelen, W. (The American Journal of Sports Medicine, 2004)
Background: Ankle sprains are the most common injuries in a variety of sports. Hypothesis: A proprioceptive balance board program is effective for prevention of ankle sprains in volleyball players. Study Design: Prospective controlled study. Methods: There were 116 male and female volleyball teams followed prospectively during the 2001-2002 season. Teams were randomized by 4 geographical regions to an intervention group (66 teams, 641 players) and control group (50 teams, 486 players). Intervention teams followed a prescribed balance board training program; control teams followed their normal training routine. The coaches recorded exposure on a weekly basis for each player. Injuries were registered by the players within 1 week after onset. Results: Significantly fewer ankle sprains in the intervention group were found compared to the control group (risk difference = 0.4/1000 playing hours; 95% confidence interval, 0.1-0.7). A significant reduction in ankle sprain risk was found only for players with a history of ankle sprains. The incidence of overuse knee injuries for players with history of knee injury was increased in the intervention group. History of knee injury may be a contraindication for proprioceptive balance board training. Conclusions: Use of proprioceptive balance board program is effective for prevention of ankle sprain recurrences.